Database for queries of melanoma cohorts with molecular and clinical data. (7th December 2022) - Philip, Manuel; Puppel, Sven Holger; Stiller, Mathias; Paschen, Annette; Roesch, Alexander; Zaremba, Anne; Schadendorf, Dirk; Horn, Susanne
Abstract: Large genome‐scale studies are deposited in various public sequence repositories. However, their access and analysis can be non‐trivial to infrequent users. Here, we present a new database connecting whole transcriptomes with clinical data for straight‐forward access and analysis of patient‐specific samples. Users can perform association tests of survival and gene expression across different cohorts, identify cell‐type expressions, or correlate the presence of immune cells. In summary, we present a new data hub for bench scientists to perform replication and discovery studies.